Fabrication and characterization of carboxymethyl chitosan/poly(vinyl alcohol) hydrogels containing alginate microspheres for protein delivery. (July 2015) - Liu, Quan; Zuo, Qinhua; Guo, Rui; Hong, An; Li, Chenghua; Zhang, Yi; He, Liumin; Xue, Wei
In this research, a novel drug delivery system consisting of alginate microspheres and carboxymethyl chitosan/poly(vinyl alcohol) hydrogel was developed for prolonged and sustained controlled drug release. The alginate microspheres and various volume ratios of carboxymethyl chitosan were incorporated physically into poly(vinyl alcohol) to form the composite system. Scanning electron microscope, rheometer, differential scanning calorimetry, and thermogravimetric analysis were used to investigate the morphological, rheological, and thermal properties. The adsorptivity and hydrogel content were evaluated by swelling ratio and gel fraction, respectively. Incorporation of alginate microspheres improved the swelling ratio and thermal stability of carboxymethyl chitosan/poly(vinyl alcohol) hydrogel. Carboxymethyl chitosan decreased gel fraction and elasticity while increased swelling and porosity of hydrogel. In vitro, the release profiles of bovine serum albumin from the composite gels were sustained for 2 weeks in phosphate buffered saline.